Development of Busy Book Learning Media to Improve the Ability to Recognize Alphabet Letters for Raudhatul Athfal Students - Widiyanti, Lilis; Akbar, Muhammad; Nurhayati, Nurhayati (Lembaga Penelitian dan Pendidikan Mandala, 2025)
his study aims to develop the Busy Book learning media to enhance early childhood recognition of alphabet letters at Raudhatul Athfal Al Mawaddah Warrahmah Kolaka. The research method used is Research and Development (R&D), which includes needs analysis, design, validation, trials, and evaluation. Validation was conducted by media and content experts to assess the feasibility of Busy Book as a learning medium. The validation results indicate that the aspects of design, clarity, and efficiency were rated as highly valid by media experts, with an average score of 4.47. Meanwhile, content experts rated the presentation and ease of use as highly valid, with an average score of 4.22, although the language aspect was categorized as valid with a score of 3.6. Practicality tests showed that Busy Book is highly practical, with a 96.15% score for attractiveness and an average of 80% for content, language, and illustrations. Effectiveness tests revealed that 70% of students reached the